Determination of fluoroquinolones in bovine milk samples using a pipette-tip SPE step based on multiwalled carbon nanotubes prior to CE separation - Springer, Valeria Haydee (2013)
A simple CE–UV method was developed for the simultaneous determination of ciprofloxacin, norfloxacin, and ofloxacin in milk samples. The optimum separation was obtained using a 20 mM ammonium dihydrogenphosphate solution with 2 mM cetyltrimethylammonium bromide at pH 3.0 as the BGE. Satisfactory resolution for structurally very similar analytes, like norfloxacin and ciprofloxacin, was achieved without including any organic solvent. Milk samples were prepared using a simple/extraction procedure based on acidic protein precipitation followed by an SPE step using only 5 mg of multiwalled carbon nanotubes as the sorbent material. The LODs for the three compounds were between 7.5 and 11.6 μg/L and the RSDs for the peak areas were between 2.6 and 4.9%. The complete method was applied to spiked real milk samples with satisfactory recoveries for all analytes (84–106%).